DFT Study for Characterization the Biological Activity of New Derivatives of Titanium (IV) Budotitane Complex - Ahmed Abdul Sattar Ali (Journal of Global Pharma Technology, 2018)
The official use of organometallic complexes in chemotherapy dating back to 1969 when cis-platin "cis-diamminedichloroplatinum(II)" showed to have properties against tumors such as“ human testicular, ovarian, bladder, head and neck carcinomas” Titanium (IV) compounds are one of the promising alternatives and candidates drugs to anti-cancer treatments that have a wide spectrum of activity against tumors. These compounds are more effective and have less side effects than platinum compounds. In this work, we characterization the building and designing geometrical shape and crystal structure of six titanium complexes "titanium budotitane complexes (IV)" depending on the DFT "density functional theory" method survey of the title complexes were performed using the Gaussian 03 (2003) program. The study also include discuss "crystal structure information, Mulliken charges allocation, complex biological effectiveness, frontier molecular orbital energies (HOMO, LUMO) of the complexes, ionization energy (IE), hardness (η), electron affinity (EA), stability, and polarity" of titanium complexes with comparition. The results show that best one of the building complexes as anticancer activity is complex 5 (C5), then complex 6 (C6)are gave lower activity than (C5) and higher when compared with other complexes, while the other complexes (C2, C1, C3, C4) respectively gave lower activity than (C5,C6) complexesKeywords: Tumors; Budotitane; Titanium (IV) metallodrug; Titanocene; Density functional theory (DFT);(HOMO, LUMO) energies.